Cryopreservation of primary neonatal rat oligodendrocytes and recapitulation of in vitro oligodendrocyte characteristics - Kim, Hanki; Kim, Bum Jun; Koh, Seungyon; Cho, Hyo Jin; Kim, Byung Gon; Choi, Jun Young (Frontiers in Cellular Neuroscience, 2025)
IntroductionIn vitro, primary rat oligodendrocytes (OLs) are widely used for research on OL development, physiology, and pathophysiology in demyelinating diseases such as multiple sclerosis. Primary culture methods for OLs from rats have been developed and improved over time, but there are still multiple aspects in which efficiency can be boosted.MethodsTo make use of excess oligodendrocyte progenitor cells (OPCs) from primary cultures, a cryopreservation process utilizing a commercially available serum-free cryopreservation medium was established to passage and freeze OPCs at −80°C for later use.ResultsCryopreserved OPCs stored for up to 6 months were viable, and retained their OL lineage purity of ~98%. While OPCs cryopreserved for 3–6 months showed a decrease in cell density after two days of proliferation, ~17% of cryopreserved OPCs maintained the potential for proliferation comparable to control OPCs that had not frozen. After induction of differentiation for four days, ~43% of both control and cryopreserved OPCs differentiated into mature OLs, and when differentiation was induced on aligned nanofibers mimicking axonal structure, myelin sheath-like structures indicative of in vitro myelination was observed in all experimental groups.ConclusionThe validation of cryopreserved primary OLs as a functionally robust in vitro model can help improve the efficiency of primary OL culture, expand its applications, and reduce the inevitable sacrifice of animals.